49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3657
|View full text |Cite
|
Sign up to set email alerts
|

Deflagration to Detonation Transition by Hybrid Obstacles in Pulse Detonation Engines

Abstract: A hybrid DDT enhancement device comprising obstacles of orifice plates and vortex generators is investigated to achieve reliable and repeatable detonations in Pulse Detonation Engines. The vortex generator is capable of yielding homogenous mixing while detonation transition can be achieved by it. The experimental results of deflagration to detonation transition process by a series of designed obstacles are reported. All experiments were carried out using a valveless PDE operated for multiple cycles using stoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The study used ten hybrid obstacle configurations comprised of the above mentioned devices. It was concluded that the DDT transition takes place following the obstacle termination more frequently than within the obstacles and that the effectiveness of DDT enhancement devices is dependent on the operating frequency of the PDE (Li, Teo, Lim, Wen, & Khoo, 2013). Computational research performed by Gamezo shows that small spacing between obstacles initially accelerated the flame faster but the spacing must then be large enough for Mach stems to form.…”
Section: Literature Survey and Experiments Conductedmentioning
confidence: 99%
“…The study used ten hybrid obstacle configurations comprised of the above mentioned devices. It was concluded that the DDT transition takes place following the obstacle termination more frequently than within the obstacles and that the effectiveness of DDT enhancement devices is dependent on the operating frequency of the PDE (Li, Teo, Lim, Wen, & Khoo, 2013). Computational research performed by Gamezo shows that small spacing between obstacles initially accelerated the flame faster but the spacing must then be large enough for Mach stems to form.…”
Section: Literature Survey and Experiments Conductedmentioning
confidence: 99%
“…It differs from conventional propulsion systems from two aspects: unsteady operation and detonation combustion 18,19 . This promising new engine uses a detonation wave which is extremely fast and a thermodynamically efficient process for converting chemical energy in a combustible mixture D to mechanical energy and tremendous kinetic energy 2,3,20,21 as compared to deflagration wave in the combustion process 22 .…”
Section: Applicationsmentioning
confidence: 99%
“…It produces kinetic energy two orders of magnitude higher than a slower-burning deflagration and four orders of magnitude higher in terms of heat release 2 . It is thermodynamically more efficient and has a real potential for the next generation of aerospace propulsion systems 3 . Detonative combustion utilises shocks or detonation waves which act as valve between the detonation product fresh charges 4 and the first practical application of non-isobaric heat addition in Humphrey cycle analysis 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Pulse detonation engine (PDE), as one of the innovative propulsion device which generates thrust by pulse detonation wave, has attracted great attentions due to its simple structure and higher thermal efficiency. 1–3 Compared with the single tube PDE, the multi-tube PDE with increased detonation tubes has the advantages of stable thrust and wide thrust range. The fundamental researches of the multi-tube PDE have been carried out by various experiments.…”
Section: Introductionmentioning
confidence: 99%